Penerapan Terapi Bermain Boneka Tangan Terhadap Kecemasan Anak Usia Prasekolah di RSUD dr. Soeratno Gemolong - Putri Sari Dewi; Anjar Nurrohmah; Fitria Purnamawati (Yayasan Literasi Sains Indonesia, 2023)
Hospitalization is a condition in which a person experiences compulsion to be hospitalized and can make a child feel uncomfortable, threatened, which causes anxiety. Efforts to reduce anxiety can use hand puppet play therapy. Hand puppets are games that are played using hand puppets and make children imagine using storytelling techniques. Knowing the results of the implementation of hand puppet therapy on the level of anxiety due to hospitalization. Using a case study design, the subject is 2 preschool-age children who are treated in the Children's Room of RSUD dr. Soeratno Gemolong. The measurement tool for anxiety uses the FIS and SCAS anxiety scales. The application was carried out 2 times in 2 days. The anxiety level of FIS and SCAS before the hand puppet therapy was carried out, the two subjects were different. Subject 1 had a higher level of anxiety (FIS: severe anxiety and SCAS: severe anxiety) than subject 2 (FIS: moderate anxiety and SCAS: moderate anxiety). Hand puppet play therapy in preschool age children (3-6 years) can reduce children's anxiety levels.